Perceived Barriers to Publication in Scholarly Journals by Faculty from Maharajgunj Medical Campus - Dahal, Samarika; Shrestha , Gentle Sunder; Singh , Shreejana; Raj Joshi , Deepak; Situala , Ranju; Raj Chalise , Pawan; Raj Sharma , Mohan (Journal of Nepal Health Research Council, 2022)
Background: Due to multiple reasons, the faculty members in Nepal devote less than expected time to research and publication. This could be attributable to various challenges unique to each faculty member and their institution. The present study aims to evaluate the potential barriers to publication faced by the faculty of Maharajgunj Medical Campus, Kathmandu, Nepal.Methods: This cross-sectional observational questionnaire-based study was conducted among the 139 faculty members representing various departments of MMC. Results: The significant barriers were: difficult coordination (43.2%), the response time of the reviewer (48.2%), overburdened with work (39.6%), lack of funds for research (44.6%), limited submission skills (33.8%), poor writing skills (35.3%), difficulties in starting to write (42.4%), lack of time to submit a paper (43.9%), and family commitment (36.7%). Conclusions: The findings of this study could be used to advocate for a prospective change in the work module to produce competent medical researchers generating high-quality publications. Keywords: Academia; low-income countries; publication, research